2019
DOI: 10.1371/journal.pone.0215900
|View full text |Cite
|
Sign up to set email alerts
|

Academic outcomes following adolescent sport-related concussion or fracture injury: A prospective cohort study

Abstract: Objectives The objectives were 1) to compare the effects of adolescent sport-related concussion (SRC) and sport-related extremity fracture (SRF) on academic outcomes including change in school grades and school attendance; and 2) to determine which specific academic accommodations were most helpful during recovery from these injuries. Methods A prospective cohort study was conducted to compare changes in school grades, school attendance and academic accommodations among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 29 publications
0
34
0
Order By: Relevance
“…In a 2019 paper, Russel et al conducted a prospective cohort study to once again show that no significant difference existed between pre-injury vs. post-injury overall or core grades amongst SRC students. In relation to accommodations, 53.1% of students with SRC reported their school was very accommodating [ 15 ]. Following a cross-sectional study, Moore et al reported that the arithmetic score was significantly lower in the concussion group when compared to the control group.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In a 2019 paper, Russel et al conducted a prospective cohort study to once again show that no significant difference existed between pre-injury vs. post-injury overall or core grades amongst SRC students. In relation to accommodations, 53.1% of students with SRC reported their school was very accommodating [ 15 ]. Following a cross-sectional study, Moore et al reported that the arithmetic score was significantly lower in the concussion group when compared to the control group.…”
Section: Resultsmentioning
confidence: 99%
“…In one study analyzing the perspectives of the adolescent athlete, found that not being able to keep up with school-work, missing academic activities, and losing the ability to successfully complete activities, was distressful [ 7 ]. Several studies demonstrated an increased likelihood of a decline in measured academic performance following SRC [ 14 , 15 ]. Prior to resumption of academic work, it is important to assess a student’s readiness to return to learning [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations